Análise da influência do tipo de argamassa colante e do tempo em aberto na aderência em parede de concreto moldada in loco - Rodolfo Rabelo Neves (2021)
The coating system execution on concrete wall castes in place must observe the peculiarities of this construction system to ensure that the coating system will present the expected performance during its useful life. Several factors are associated with the detachment of ceramic tiles seated on the concrete substrate, being the type of mortar cited as one of the most influential. Although studies have already been carried out on the laying of ceramics on the concrete substrate, few have evaluated the detachment with a focus on the constructive system concrete wall castes in place. Therefore, this work aims to evaluate the influence of the type of mortar on the detachment of ceramic tiles, observing the conditions associated with the mentioned construction system. It was observed that the granulometry and type of aggregate were the factors that most influenced the performance of the adhesive mortars, and the lower content of fines and the use of natural aggregates are beneficial factors for the adhesive mortars. Furthermore, longer opening times proved to be factors that reduce the average tensile adhesion strength.